Respostas

2013-06-03T22:36:48-03:00

x-2y=8  ------------>  x=8+2y

2x-3y=11

 

 

2(8+2y)-3y=11

16+4y-3y=11

16+y=11

y=-5

 

x-2(-5)=8

x+10=8

x=-2

 

x=-2 e y=-5

1 5 1
2013-06-03T22:39:46-03:00

Vamos chamar o primeiro numero de x e o segundo de y

 

 

\left\{\begin{matrix} x - 2y = 8\\ 2x - 3y = 11 \end{matrix}\right.

 

x-2y = 8\\ x = 8+2y\\

 

Substituindo na segunda equação:

 

2x-3y = 11\\ 2(8+2y)-3y = 11\\ 16 + 4y - 3y = 11\\ 16 + y = 11\\ y = 11-16\\ y = -5

 

Agora descobrindo o valor de x:

 

\\x-2y = 8\\ x - 2(-5) = 8\\ x+10=8\\ x = -2

 

1 5 1